Ecological Interactions Between Camellia oleifera and Insect Pollinators Across Heterogeneous Habitats - Linqing Cao; Qiuping Zhong; Chao Yan; Xiaoning Ge; Feng Tian; Yaqi Yuan; Jinfeng Wang; Jia Wang; Shengtian Chen; Hong Yang (Insects)
Camellia oleifera is an important woody oil plant in southern China, and developing its industry can enhance forest resource uses and increase edible oil supply. This study investigated the floral characteristics of different C. oleifera varieties, analysed the species and diversity of flower-visiting insects in different habitats, identified the main pollinators and their flower-visiting behaviours, and explored the relationship between pollinating insects and their floral characteristics. The floral lifespan of individual C. oleifera flowers was 5–8 d across cultivars, which is essentially the same. However, floral traits and nectar sugar composition exhibited distinct differences. There were 22 species of insect pollinators from 14 genera and 8 families, including Hymenoptera and Diptera, in 3 habitats. High-potential pollinators varied by habitat, with Apis cerana and Phytomia zonata being the most frequent. A comparison showed that A. cerana was the best pollinator, whereas P. zonata had a larger population, was not affected by oil tea nectar poisoning, and could still pollinate. Therefore, the contribution of P. zonata cannot be overlooked. Redundancy analysis revealed the response relationship between the floral traits of C. oleifera and three insect population characteristics. Stamen length was the main floral trait affecting insect populations.